Rancang Bangun Kepuasan Konsumen Pada PT. Jaya Diesel Dengan Metode Importance Performance Analysis Berbasis Web - Henry Aditya Syahputra; Nidia Enjelita Saragih (Himpunan Penggiat Teknologi Informasi Abrar Indonesia, 2023)
The consumer satisfaction system created in this research is by using the IPA method. Customer satisfaction is the result that consumers feel from the company's process activities, the results of which are in accordance with consumer expectations. Customers are satisfied when their expectations are met and are very happy when their expectations are exceeded. Customer satisfaction is closely related to quality, which directly affects product performance. Service quality is closely related to customer satisfaction. The development of the company is influenced by the company's ability to serve its customers. The services offered by the company must pay attention to the quality standards offered to customers and even exceed the efficiency expected by the customer, so that customer satisfaction is easily achieved by the company because it can make customers continue to use the company's services.